PENERAPAN APLIKASI DALAM MENGOLAH ASET DESA (STUDI KASUS : KEPENGHULUAN SRI KAYANGAN) - Sihombing, Volvo; Yanris, Gomal Juni (Pelita Nusantara Medan, 2020)
Utilization of Village assets is indirectly used in the context of carrying out village government duties and does not change ownership status. Permendagri No.1 Tahun 2016 village is a legal community unit that has the authority to manage and manage government affairs, the interests of the local community based on community initiatives. With the advancement of data collection technology village assets pursued in the form of digitalization in the form of buildings, land or the others. Kepenghuluan (Village Office) Sri Kayangan in managing village assets is still conventional which is recorded in the book. With the application of the system that was built, the archives of all the assets of the village of Keprihuan Sri Sri could be audited properly.Keywords: assets, village, database